An annotated checklist of fish biodiversity in the Muara Angke Wildlife Reserve, North Jakarta, Indonesia - Gema Wahyudewantoro; Rahmi Dina; Sekar Larashati; Wisny Haryanti; Riza Rahman Hakim; Muhammad Haikal Abdurachman; Yoga Candra Ditya (Fisheries and Aquatic Sciences)
Muara Angke Wildlife Reserve is the protected area for mangrove ecosystem in Jakarta. This area has a wealth of biodiversity, both flora and fauna, especially fish. This study presents an updated checklist of fish species that have been recorded in the waters of the Muara Angke Wildlife Reserve. The results of the information obtained are 43 species from 29 families. The data includes six newly mapped families: Engraulidae, Zenarchopteridae, Ambassidae, Butidae, Oxudercidae, and Osphronemidae. In addition, thirty-three synonym names have been validated. Cyprinidae (4 species) and Ambassidae (3 species) are the families with the largest species. 87.80% euryhaline species, 12.20% freshwater species, and 63.41% migratory species (amphidromous, anadromous, catadromous, oceanodromous, and potamodromous). In addition to native fish, there are seven species of introduced fish, completing the variety of species in the area. With biodiversity, especially fish in Muara Angke Wildlife Reserve, it is expected to be a common concern for all parties to be actively involved in maintaining the sustainability of fisheries resources.